Acoustic Emission Characteristics of Normal and Layered Concrete Blocks during Dilating/Static Fracture. (8th January 2020) - Ma, Ji; Du, Feng; Zhang, Shuai
Abstract : Static fracturing technology is one of the most effective methods for localized breaking of rock and concrete. Layered concrete and rock structures are commonly seen in engineering applications such as breaking of concrete buildings, stone cutting, and excavation of rock in underground spaces. Therefore, it is essential to study the static fracturing characteristics of layered concrete to ensure the safety of engineering construction processes. In this paper, using acoustic emission (AE) technology and surface displacement monitoring, the deformation and fracturing of ordinary-strength concrete, concrete with a soft interlayer, and layered concrete (with strength decreasing successively by layer) were studied under the effect of a static (or soundless) cracking agent (SCA). The experimental results indicated that (1) AE activity of the two layered concrete test blocks during static fracturing showed a gradually increasing trend, while that of the ordinary-strength concrete tended to first increase and then decrease; (2) for the concrete test block with a soft interlayer sandwiched by high-strength layers, the AE events reached a maximum in the transfer of expansion pressure stage, which accounted for 47.11% of the total value in static cracking; the macroscopic damage to layered concrete test blocks comprising multiple interlaid layers with different strengths mainly occurred in the fracturing stage, during which the AE events and AE energy accounted for 76.22% and 66.94%, respectively, of those in the whole static fracturing process; and (3) the duration of static fracturing prolonged with the increase of the overall strength of the concrete test blocks. The results provide a useful experimental reference for the application of static fracturing technology in the breaking of layered concrete and rock.